Russian Private Equity Market - КокоревДмитрий Александрович (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
This article is a short review of main reports, that were presented at the Private Equity Conference, which was organised in Moscow on October, 29 by CBonds agency, Russian Private Equity Journal and MICEX Group. Kokorev Dmitry Aleksandrovich. Research Assistant of Corporate Finance Centerdkokorev@gmail.com